CALCIUM SULFATE SCALE IN THE PETROLEUM INDUSTRY - Hadi Poernomo; Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2004)
Oilfield scale is defined as the precipitation of hard, adherent deposits of inorganic solid originating from aqueous media. This constitutes sulfate and carbonate of the alkaline earth metals calcium, barium and strontium and complex salts of iron. Generally, the process of the scale deposition occurs when the product solubility of a compound considered is exceeded. The formation of scale, such as calcium sulfate, has long recognised as one of the serious problems in oil and gas production leading to reduced production rates as flow becomes restricted. Calcium sulfate scale found in the oilfield is in the form of gypsum (CaSO4, 2H2,0) which is the most stable form at temperatures of 40 Â°C or less at atmosphere pressure. Above this temperature, anhydrite (CaSO4,) may be found, although hemihydrate (CaSO. 1/2H,O) may form under certain conditions. The reaction for precipitation of calcium sulfate is as follows: Ca+2 (aq) + so4-2 (aq) = CaSO4 (solid) The solubility of calcium sulfate in distilled water is 2080 mg/l at 25